Predict location(s) of Apis dorsata nesting sites using remote sensing and geographic information system in Melaleuca forest - Saberioon, Mohammadmehdi; Mardan, Makhdzir; Nordin, Laili; Mohd Sood, Alias; Gholizadeh, Asa (Science Publications, 2010)
Problem statement: The Asiatic Giant honeybees (Apis dorsata) are seasonally abounded throughout the upland and lowland rainforests in South East Asia. The colonies of A. dorsata are found to nest in aggregates on tall bee trees (tree emergent) in the open, as well as, nesting singly in concealed locations when nesting low, especially in the submerged forest of Melaleuca cajuputi as in the vast hectare of Melaleuca forest along the coastal areas of Terengganu. The trunk and branches of the Melaleuca trees are almost upright and the bark are papery and loose that it is unsuitable to serve as nesting support for A. dorsata. Therefore, other trees with sloping branches in the vicinity of the Melaleuca forest are chosen as nesting supports for the A. dorsata colonies. Melaleuca cajuputi and Acacia auriculiformis trees are major sources of nectar and pollen for A. dorsata. Approach: A pilot study were conducted to determine the vegetation distribution area of Melaleuca cajuputi and Acacia auriculiformis, colony distribution and density Apis dorsata colonies using the remote-sensing and field survey by GPS hand held in the submerged Melaleuca forest around the village of Gong Beris, Marang district, Terengganu (Upper left 5°2’19.223”N, 103°10’4.092”E and lower down 4°53’42.31”N, 103°22’37.90”E). Result: Based on the map and field survey, it is clear that almost all Apis dorsata nesting sites were located in the Acacia auriculiformis areas Melaleuca cajuputi is mostly using by Apis dorsata as source of nectar and pollen in Marang district, Malaysia Conclusion: The outcome on the distribution area and feral colonies nesting sites will be used to propose the locating of possible A. dorsata nesting sites and understand better nesting behavior of Apis dorsata to improvement searching ability for honey hunters in Marang district.